POLICY IMPLEMENTATION OF VILLAGE FUND ALLOCATION IN SANSARINO VILLAGE, AMPANA CITY DISTRICT, TOJO UNA-UNA REGENCY: A CASE STUDY - Fitrina, Fitrina; Khattab, Syahrudin; Haryono, Dandan (Penerbit Lafadz Jaya, 2024)
This study investigates the implementation of the Village Fund Allocation policy in Sansarino Village, Ampana City District, Tojo Una-Una Regency. Utilizing a qualitative descriptive approach, this research identifies factors influencing the policy’s effectiveness, including standards, resources, communication, and the socio-economic environment. Data were collected through purposive sampling, involving key informants such as village officials and community members. The analysis applies Van Meter and Van Horn’s policy implementation model. Results indicate significant challenges, including resource inadequacies, lack of coordination, and discrepancies between policy objectives and community needs. Recommendations include enhancing human resources, fostering collaboration among stakeholders, and ensuring better alignment between policy goals and local contexts. This study contributes to the discourse on public policy implementation in rural settings.